PENGEMBANGAN KAPAL PERIKANAN TRIMARAN: KAJIAN MENGENAI KEBUTUHAN TENAGA KAPAL, KEAMANAN DAN KENYAMANAN - Richard B. Luhulima (Fakultas Teknik Universitas Pattimura, 2021)
In general, the fishing fleets operating in Maluku waters are consisted of monohull and trimaran vessels with outriggers managed by local entrepreneurs. Monohull fishing vessels have limited deck space and low transverse stability, whereas trimaran fishing vessels have more deck space and greater transverse stability than monohull fishing vessels, but space is still limited due to their outrigger shape. This study aimed to analyze the development of the trimaran fishing vessel in terms of energy requirements, safety and comfort of the crew during fishing operations. At the beginning of this research, data analysis was undertaken and the basic size of monohull fishing vessels operating in Maluku waters, from this data the shape of the trimaran hull was then designed. Resistance was calculated using CFD, and then the resistance, stability, safety, and comfort of the ship were examined using Maxsurf. The trimaran vessel’s barrier was 8.86% smaller than a monohull and 3.25% smaller than a catamaran. Trimaran vessels consumed more energy than other vessel types. The average trimaran period was 10.5 seconds which met IMO standards and was declared as operationally good.